Pengembangan Media Pembelajaran Interaktif Swishmax Berbasis Android pada Mata Pelajaran SBdP Siswa Kelas III SDN Kalibata 07 Jakarta Selatan - Brahmana, Samuel; Amelia, Winda (Ikatan Da'i Indonesia, 2024)
This research has two objectives to be developed, namely knowing the design and development of Swishmax media in learning arts and culture and crafts (SBdP) for class III students at SDN Kalibata 07 South Jakarta, knowing the feasibility and effectiveness of Swishmax media in learning arts and culture and crafts (SBdP) for class III students at SDN Kalibata 07 South Jakarta. In developing this media, a research method was used, namely Research and Development (R&D) with the Dick and Carrey research model which consists of 10 research stages. The results of the research carried out by the researcher obtained a percentage of 90% by material expert validators, a percentage of 90% from the language expert validator test, a percentage of 80% from the media expert validator test. The feasibility test results in the small group were obtained with a percentage result of 82%, the feasibility test results in the large group were obtained with a percentage result of 92%.